Application of Remote Sensing Data for Slum Identification Using Geography Information System (Case: Former Harbor, Singaraja City) - Ruhilatul Janah; A Sediyo Adi Nugraha (Media Komunikasi FPIPS, 2021)
This research was conducted in Singaraja City using high-resolution remote sensing images and geographic information systems. The purpose is to use remote sensing images and geographic information systems to identify slum settlements, especially the former harbor area in Singaraja City. Slum settlement is the impact of population growth that is difficult to control. As a result, the remote sensing image can identify three features: slums, non-slum settlement, and non-slum areas. Most slum settlements are located in coastal areas, and non-slum settlements are located in areas close to economic locations and tourist sites and offices. The most significant introduction to slum identification comes from the building area. Based on these results, it can be concluded that slum settlement can be identified through images obtained from Google earth and recognized visually through interpretation keys.